The global leadership initiative on malnutrition criteria for the diagnosis of malnutrition in patients with chronic liver diseases: a systematic review and meta-analysis - Zhiming Wang; Yuping Cao; Yumei He; Menghao Hao; Shiyan Wu; Lu Li; Qiong Wang; Xiaobin Sun; Xiaobin Sun; Liping Wu; Liping Wu (Frontiers in Nutrition)
BackgroundMalnutrition in patients with chronic liver disease (CLD) is linked to increased mortality and a high risk of morbidity. Assessing the nutritional status of patients with CLD is challenging. The Global Leadership Initiative for Malnutrition (GLIM) offers a novel diagnostic framework for malnutrition. However, the efficacy of GLIM in CLD patients has not been validated.MethodsA systematic review and meta-analysis were conducted to evaluate the utility and diagnostic accuracy of the GLIM criteria in adult patients with CLD, involving a search of seven databases for relevant studies. The evaluation of quality was conducted with the QUADAS-2 tool.ResultsThe analysis included a total of five studies. Sample size ranged from 109 to 406 among different studies. According to the GLIM criteria, around 21.2 to 69.9% of individuals were identified as having malnutrition. Simultaneously, the subjective global assessment (SGA) detected malnourished patients ranging from 35.0 to 86.0%. Five studies compared the GLIM with the SGA. The nutritional assessment process in the studies was not clear according to the QUADAS-2 tool. The overall specificity of the meta-analysis was 85.8% (95% CI: 82.5–88.7%) and the overall sensitivity was 49.1% (95% CI: 45.5–52.8%).ConclusionThis is the first systematic review and meta-analysis on GLIM criteria, SGA and CLD patients. The applicability and reliability of the GLIM criteria in CLD patients remain constrained. Furthermore, certain validation studies that are parallel and predictive may have methodological limitations. Additional research is needed to confirm the applicability of the GLIM criteria in patients with CLD.Systematic review registrationPROSPERO, CRD420251010347.